Staff empowerment and engagement in a magnet® recognized and joint commission international accredited academic centre in Belgium: a cross-sectional survey - Peter Van Bogaert; Danny Van heusden; Stijn Slootmans; Ingrid Roosen; Paul Van Aken; Guy H. Hans; Erik Franck (BMC, 2018)
Abstract Background A substantial number of studies linked aspects of a balanced, healthy and supportive nurse practice environment with quality and patient safety. To what extent balanced work characteristics such as social capital, decision latitude and workload are relevant for all staff engaged in patient care including healthcare and medical staff in a Magnet Recognized and Joint Commission International accredited academic centre is unclear. The study aim is to investigate associations between work characteristics such as social capital, decision latitude and workload, work engagement and feelings of burnout as explanatory variables and job satisfaction, turnover intentions and perceived quality of care as dependent variables in a study population of nursing, healthcare and medical staff taken in account generation differences. Methods Hierarchical regression analysis estimated strength of associations with demographic characteristics (block-1), professional category (block-2), work characteristics (block-3) and work engagement or burnout dimensions (block-4) as explanatory variables of job satisfaction and turnover intention and quality of care as outcome variables. Results The study confirmed and extended previous study findings demonstrating positive impact on staff' job outcomes and assessed quality of care by balanced work characteristics such as social capital, decision latitude and workload in nursing staff (N = 864), healthcare staff (N = 131) and medical staff (N = 241). Generational characteristics and professional category were associated with turnover intentions and less favorable assessed quality of care, respectively. Explained variances of studied models ranged from 14.4 to 45.7%. Conclusion Engaging and committing staff to promote excellent patient outcomes in daily interdisciplinary practice works through clear frameworks, methods and resources supported by governance and policy structure that makes outcomes visible and accountable.